Translating behavior analytic terminology: semantic and etymological considerations from a Russian perspective. Issue 1 (2nd January 2019) - Alipov, Nikolay; Qamar, Zukhra; Martin, Neil
ABSTRACT: Behavior Analysis is a relatively young but rapidly evolving scientific field, that requires a scientifically based and conceptually systematic vocabulary. Basic principles for translating behavior analytic terms have previously been established, concerning both the morphology (topography) of the terms and their content (function). In the present paper, and based on our experience of translating behavior analytic terms into Russian, we seek to expand consideration of the functional issues by adding some generalizations as an extension to previous established translation principles. Although the starting premise when selecting a behavior analytic term is that it belongs to a distinct and well-developed field with its own conceptual and theoretical basis, we also acknowledge the earlier academic roots and wide overlap with many other related disciplines. Thus, when selecting a term, it is essential to conduct a semantic and etymological analysis, addressing the following issues: 1) historical continuity; 2) links with related disciplines; 3) potential uniqueness of a term (use of specific neologism) within the field of behavior analysis.